EFL teachers' teaching with video-conferencing and additional technology: A systematic literature review - Ibrahim Mohammad (Universitas Negeri Semarang, 2025)
This systematic review aimed to contribute to insights into the vital role of implementing independent ICT tools in teaching with video-conferencing (VC). The study focused on what technological tools EFL teachers’ use in VC-based contexts, how and why teachers use these tools, and the impact of the tools on the development of students’ language skills. The analysis of 64 studies published between 2010 and 2022 indicated that teachers mostly use learning management systems and various additional tools such as PowerPoint slides, websites, and online quizzes. The results also indicate that the number of studies that targeted speaking skills was higher than those that focused on other skills, with reading being investigated by very few studies. Concerning the challenges, a lack of digital preparedness on the part of both students and teachers was reported. The impact of these tools was mostly positive in terms of raising the interaction and communication elements along with skills improvement. The findings can be beneficial for EFL teachers, course designers and EFL trainers in VC-based contexts by developing their awareness of the necessity of implementing specific technological tools to gain the expected skills-related outcomes.